An evaluation of the impact of attachment and trauma training for pupil referral unit staff. (June 2020) - Greenhalgh, Rebecca; Fflur, Siana; Donnelly, Katherine; Kirkaldie, Helen; McDonnell, Lynn
Background: The Gwent Attachment Service trained four pupil referral units (PRUs) staff in attachment- and trauma-informed work. Education staff received 2 days of training and then attended six skills development sessions (SDSs) on a monthly basis to embed the training concepts into their work. This model takes a "whole systems approach" to intervention, drawing on evidence suggesting that having a supportive and consistent system around a child that takes into account their attachment needs leads to better outcomes. Methods: Self-reported knowledge of attachment- and trauma-informed work, confidence in carrying out this work, and worries about implementing this work were collected from 64 education staff members across the four PRUs. Measures were repeated at three time points: pre-training, post-training, and post-SDS. Results: Knowledge and confidence increased from pre- to post-training. Knowledge did not significantly differ between post-training and post-SDS. Confidence was lower at post-SDS than post-training but remained above pre-training ratings. Worries decreased from pre- to post-training and decreased again post-SDS. Conclusion: Training and SDSs can improve teaching staffs' perception of their knowledge and confidence, while reducing worries about working in an attachment- and trauma-informed way. SDSs decreased worries about working in an attachment- and trauma-informed way over and above training alone, indicating that the SDSs contribute added value. This study presents a promising starting point for improving the lives of children and young people who have experienced trauma and have attachment difficulties.